Financing Structure and Liquidity Risk: Lesson from Malaysian Experience - Abdul-Rahman, A.; Said, N.L.H.M.; Sulaiman, A.A. (Walter de Gruyter GmbH, 2017)
This study examines the relationship between financing structure and bank liquidity risk. We compare the findings between Islamic and conventional banks for the case of Malaysia. We adopt four measures to represent financing structure; namely 1) real estate financing, 2) financing concentration, 3) stability of short-Term financing structure and 4) stability of medium-Term financing structure. Two BASEL III liquidity risk measures are tested; namely, liquidity coverage ratio (LCR) and the net stable funding ratio (NSFR) to measure short-And long-Term liquidity risk, respectively. Based on panel data regression comprising 27 conventional and 17 Islamic banks from 1994 to 2014, our findings show that real estate financing and stability of short-Term financing structure for Islamic banks are positively related to both liquidity risk measures. This implies that an increasing number of real estate financing and a stable short-Term financing structure may increase Islamic banks' short-And long-Term liquidity risks. However, although real estate financing does not affect conventional banks' liquidity risks, a stable short-Term financing structure and increasing financing concentration can positively influence bank long-Term liquidity risk. Our findings shed light crucial policy implications for regulatory bodies and market players in the context of liquidity risk management framework as well as the need to develop a separate framework between conventional and Islamic banking institutions.